Modelo estructural de riesgo de crédito con intensidad estocástica de covariables observables y un factor de fragilidad determinado a partir de un proceso de saltos (2019)
In this work, the parameters for the default intensity of observable covariates in the presence of an unobservable fragility factor are estimated. The observable information corresponds to the evolution In this work, the parameters for the default intensity of observable covariates in the presence of an unobservable fragility factor are estimated. The observable information corresponds to the evolution of some macroeconomic variables over time, as well as the characteristic information of the individuals of a credit segment in a Colombian financial entity; a small modification to the Cox process proposed for intensity is made in Duffie et al. (2009), in order to include a jump component by means of which it is sought to describe the spontaneous clusters defaults, a program is finally implemented to estimate the parameters associated to the process for intensity by means of the EM algorithm and the Gibbs sampler.